Odpowiedzi

2009-10-13T17:42:13+02:00
X-cena wisiorka
y-cena łańcuszka

x + y -105
x-8 + y + 0,2y = 100

x+y = 105 / *(-1)
x+1,2y = 108

-x-y = -105
x+1,2y = 108

0,2y = 3 /* 5
y = 15 zł

x+y = 105
x+15 = 105
x = 105 - 15
x = 90 zl

Odp:Wisiorek kosztuje 90zł.
24 4 24
2009-10-13T17:48:46+02:00
X- cena łańcuszka
y-cena wisiorka

x+y=105
1,2x+y-8=100

x+y=105 /*(-1,2)
1,2x+y=108

-1,2x-1,2y=-126
1,2x+y=108

-0,2y=-18 /: (-0,2)
y=90

Odp WISIorek kosztuje 90 zł.
12 4 12
2009-10-13T19:33:33+02:00
X-cena wisiorka
y-cena łańcuszka

x + y -105
x-8 + y + 0,2y = 100

x+y = 105 / *(-1)
x+1,2y = 108

-x-y = -105
x+1,2y = 108

0,2y = 3 /* 5
y = 15 zł

x+y = 105
x+15 = 105
x = 105 - 15
x = 90 zl

Odp:Wisiorek kosztuje 90zł.
5 5 5